Partisipasi Politik Masyarakat dalam Pemilihan Kepala Kampung (Studi Kasus Pilkam Mandouw Distrik Samofa Kabupaten Biak Numfor) - Luluk Endang Nurrokhmah; Imelda Jaquillen Loppies (Jurnal Syntax Transformation, 2021)
One of the pillars ofpri nsip democracy iselections. So that democracy can be interpreted as a government that feelsl from, by and for the people. Bthe form of participation that is very important carried out by citizens is participation in elections both national level, the level of daerah and the village level,the purpose of knowing the level of participation of the village community and factors that inhibit the political participation of the village community in participating in the election of the head of Kampung Mandouw District Samofa Biak Numfor Regency,themethod in this study uses qualitative research methods using descriptive approaches and data collection techniques using observation, interviews and documentation with data analysis techniques using qualitative data analysis techniques,the results of the polls showed that of the 2892 voters or votes in the permanent voter list (DPT) only 605 people participated in voting while 2287 people did not vote or use their voting rights. So if the percentage is only about 25% who voted in the election of the head of Mandouw Village. Many obstacles faced or become the reason for the community not to follow the pemilihan kepala kampung namely, the nature of stupid times, candidates who are whistled not as desired, and some are out of town on the grounds of work or education.